Seismic Expression of Tectonic Features in the Lesser Sunda Islands, Indonesia - Darman, Herman (Ikatan Ahli Geologi Indonesia, 2012)
The Sunda Arc is a chain of islands in the southern part of Indonesia, cored by active volcanoes. The western part of the Sunda arc is dominated by the large of Sumatra and Java, and is commonly called